Reynolds number effects on swirling flows intensity and reattachment length over a backward-facing step geometry using STD k-ε turbulence model. Issue 1 (July 2020) - Darmawan, Steven
Abstract: Swirling flow at recirculation zone of backward-facing step (BFS) geometry undoubtly affected by Reynolds number since it is involving rotational vortices. This flow behavior can be represented by flow intensity and reattachment length inside the geometry. BFS geometry is chosen for it is well-known characteristics visualizing swiriling flow that occur in many industrial application. Unfortunately, experimental method for visualizing rotational vortices over a BFS geometry oftenly involve advance technology including the image capturing devices. CFD method is use in this research for computionally visualize respected flows with Reynolds number variation with lower cost. The model is 3 dimensional with Step height (h) = 41mm, upstream height ( H) = 81mm, expansion ratio = 1.5, total length ( L ) = 4050 mm and width = 20 h . The mesh is triangular with 90.293 nodes. Reynolds numbers varied to Re = 4290.39; 6673.94; 7614.23; and 9287.29 which gained from experimental data. The working fluid is single phase air, with inlet and outlet temperature also gained from experimental data. The initial fluid temperature at inlet and outlet are 28.4°C and 28.8°C; 27.3°C and 28.6°C; 26.2°C and 28.3°C; 28.7°C and 29.8°C for respected Reynolds number variation. The flow condition is assumed transient with time step set of 1 and simulation is done with STD k-ε turbulence model. Highest Reynolds number variation reattached at reattachment / step height X/h = 6.82, compared to Re = 4290.39 with X/h = 11.71. CFD simulation results show that eddies inside the vortices and the X/h affected by floe velocity and so on with the flow temperature.